The impact of foreign investment on strengthening the security of the national economy of Ukraine and investment guidelines for Ukrainian-Polish cooperation - Savitska, Svitlana; Zabolotnyy, Serhiy (Turystyka i Rozwój Regionalny, 2024)
The article examines the theoretical foundations of the category of foreign direct investment and identifies their characteristic features. The importance of foreign investment is substantiated, and both positive and negative consequences of FDI for the country’s economy are identified. The research investigates the dynamics of the inflow and the geographical structure of foreign direct investment by country of receipt of investment, presents the largest investor countries and the most attractive sectors for investment in the Ukrainian economy, and evaluates the degree of deterioration in the investment attractiveness of the national economy. The features of Ukrainian-Polish investment cooperation are studied, and priority directions for developing investment activity are discussed.